The impact of inventory management on the performance of an organization - Emmanuel Mwamba; Tryson Yangailo (Revista Científica Profundidad Construyendo Futuro)
Inventory management is important for the successful functioning of any organization. The main core objective of this research study was to determine the impact of inventory management on the performance of an organization in the case of Tanzania Zambia Railway Authority. This study was the first to be conducted in the railway sector in an African context. The study applied descriptive research design with primary data collected using questionnaire with purposive sampling method of 21 participants as sample size. Data analysis was done using Jamovi software. The findings revealed that TAZARA uses ABC analysis in decision making but not Economic Order Quantity Model in decision making in purchasing materials. The study also reveals that the introduction of ICT through electronic management system in inventory management would improve performance and that TAZARA employees need to be trained in procurement and regulations as most of the employees are young and have less work experience.